2020
DOI: 10.1016/j.metabol.2020.154340
|View full text |Cite
|
Sign up to set email alerts
|

Disrupted endothelial cell heterogeneity and network organization impair vascular function in prediabetic obesity

Abstract: Background: Obesity is a major risk factor for diabetes and cardiovascular diseases such as hypertension, heart failure, and stroke. Impaired endothelial function occurs in the earliest stages of obesity and underlies vascular alterations that give rise to cardiovascular disease. However, the mechanisms that link weight gain to endothelial dysfunction are ill-defined. Increasing evidence suggests that endothelial cells are not a population of uniform cells but are highly heterogeneous and are organized as a co… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 96 publications
0
37
0
Order By: Relevance
“…We next asked, how does mitochondrial ATP facilitate nitric oxide-mediated vasodilation? The Ach-nitric oxide vasodilator pathway is mediated via muscarinic (M3 subtype [33]), Gαq-dependent stimulation of phospholipase C and the subsequent hydrolysis of phosphatidylinositol-4,5-bisphosphate (PIP2) to produce IP 3 , Once liberated, IP 3 activates IP 3 receptors evoke, in turn, Ca 2+ release from internal stores, Ca 2+ influx via store-operated Ca 2+ entry, and Ca 2+ -dependent activation of endothelial nitric oxide synthase [28,30]. Because functional mitochondria are required for basal (unstimulated) endothelial cell Ca 2+ signaling [34], we speculated that mitochondrial ATP synthase control of nitric-oxide mediated vasodilator signaling (Figures 1–3) arises via the nucleotide’s control of IP 3 -mediated Ca 2+ signaling.…”
Section: Resultsmentioning
confidence: 99%
“…We next asked, how does mitochondrial ATP facilitate nitric oxide-mediated vasodilation? The Ach-nitric oxide vasodilator pathway is mediated via muscarinic (M3 subtype [33]), Gαq-dependent stimulation of phospholipase C and the subsequent hydrolysis of phosphatidylinositol-4,5-bisphosphate (PIP2) to produce IP 3 , Once liberated, IP 3 activates IP 3 receptors evoke, in turn, Ca 2+ release from internal stores, Ca 2+ influx via store-operated Ca 2+ entry, and Ca 2+ -dependent activation of endothelial nitric oxide synthase [28,30]. Because functional mitochondria are required for basal (unstimulated) endothelial cell Ca 2+ signaling [34], we speculated that mitochondrial ATP synthase control of nitric-oxide mediated vasodilator signaling (Figures 1–3) arises via the nucleotide’s control of IP 3 -mediated Ca 2+ signaling.…”
Section: Resultsmentioning
confidence: 99%
“…Intracellular Ca 2+ was monitored using the Ca 2+ -sensitive fluorescent indicator, Cal-520 ( 36 , 37 ). For this, MCF-7L breast cancer cells were plated in ibidi μ-Slide 8-well culture dishes and left to adhere for 24 h (37 °C, 5% CO 2 ).…”
Section: Methodsmentioning
confidence: 99%
“…Temporal Ca 2+ signals were extracted from the raw fluorescence intensity image stacks, using 30-pixel (∼4 μm) diameter circular regions of interest manually positioned at the center of each cell. Ca 2+ signals were analyzed using a custom Python-based analysis suite as described previously ( 36 , 37 ). The average initial Ca 2+ peak response evoked by carbachol in the absence and presence of YM254890 was analyzed in GraphPad Prism, v7.01 (GraphPad).…”
Section: Methodsmentioning
confidence: 99%
“…Obesity changes the network activity and decreases the cell populations that respond to acetylcholine, causing vasodilation, increasing sensory cell clusters, and lengthening the distance for information transmission between cell clusters. For example, Wilson et al demonstrated that communication between endothelial cells is disrupted in rats with prediabetic obesity [ 50 ]. They found that obesity impaired the calcium response in the endothelial cell network, leading to insufficient endothelial vascular tone control.…”
Section: Relationship Between Diabetes and Endothelial Dysfunctionmentioning
confidence: 99%